Solar-powered biorefinery - Soo, Han Sen (2022)
‘Solar chemical’ production is typically constrained by the need for sacrificial reagents, low product values, and metal-containing catalysts. Now, hydrogen peroxide is generated from only water and air using lignin as a photocatalyst. The combination of lignin with unspecific peroxygenases enables enantioselective oxyfunctionalization of hydrocarbons.